From informal coordination to formalised policy integration: options for strengthening climate change adaptation in EU finance and trade policy - Pitzén, Samuli; Kivimaa, Paula; Hildén, Mikael; Mosoni, Claire (Frontiers in Climate, 2025)
Progressing climate change is causing a growing need for policy domains to adapt to its effects. Especially cross-border impacts of climate change are only beginning to be recognised in trade and finance. Through a qualitative analysis of 15 semi-structured interviews and 30 policy documents and reports, we examine adaptation policy integration and coherence in the European Union. Specifically, we investigate how policy actors in the trade and finance domains recognise adaptation needs and whether progress is being made. Our findings show that there has been progress mostly at the level of policy objectives and informal coordination between domains, whereas formalised actions and instruments promoting integration and coherence are emerging slowly. Moreover, we find that managing the cross-border impacts of climate change and adapting to them is demanding due to (1) the complex and interconnected ways in which impacts are transmitted, (2) the detailed understanding of the impact and response transmission systems needed for policy responses, and (3) the lack of formal integration of the climate change adaptation policy within EU trade and finance policies. Given these challenges, and the rapid advance of climate change, there is a need for high-level political commitment to progress with the preparedness for cross-border climate change impacts in trade and finance.